An Evaluation of The Inauguration Speech Made by His Excellency The President of Kenya on 28th November, 2017. - Mutune, Fellis N. (Machakos University, 2018)
An inauguration speech in any political set up seeks to give an assertion of the round map on how to address issues that directly impact on the electorate. It should also be a timely moment to thank those who voted you into office. For the speech to be described as an all encompassing one it should appeal to all people regardless of their tribe, skin colour, religion or political affiliation. This paper looks at the inauguration speech which was made by His Excellency the President Honourable Uhuru Kenyatta who is the President of the Republic of Kenya on 28th November 2017 during his swearing in Ceremony. The speech could have been seen to have been made in on an effort to elevate and justify Uhuru’s re-election both locally and internationally. Uhuru’s first victory was challenged by the National Super Alliance in the Supreme Court. The Supreme Court annulled the election citing irregularities and illegalities in the election process. The primary objective of this paper is to find out how the speech pacified the electorate who felt that his reelection was supposed to be rubbished since a majority of voters did not cast their ballots. The paper would also wish to establish how the speech appealed to the locals especially those who did not support H. E. Uhuru during the campaigns and even in the casting of the ballot. Further, the paper would also wish to establish how the speech appealed to the people living beyond borders who had harboured negative feelings about Uhuru’s re-election. Lastly, the paper strived to find out the rhetoric in H.E Uhuru Kenyatta’s speech that appeals to the audience. This paper draws upon mostly primarily source the inauguration speech which will be downloaded online from the Government of Kenya website. The data will be analyzed qualitatively since the researcher will only describe the parts of the speech that have elements of pacifications both locally and internationally and those that appealed to t. The paper adopts a rhetorical analysis to discourse analysis. The results showed that the president pacified the electorate who did vote for him through the elements of education, healthcare, economy, democracy and international community. Further the results revealed that the president appealed to the ethos, pathos and logos of the electorate. Again, he uses the first person plural pronoun ‘we’, scriptural reference and repetition of words and phrases to appeal to the voters who never supported his re-election bid. Keywords: pacify, inauguration speech, re-election, annulled, the Supreme Court
Keywords: Inauguration speech